Hubungan Penggunaan Kontrasepsi Oral dengan Kejadian ‎Kanker Payudara Di RSUD Arifin Achmad Provinsi Riau - Dewinny Septalia Dale (Jurnal Indragiri Penelitian Multidisiplin, 2023)
In North America, every 12 minutes a woman dies because of breast cancer. Breast cancer is the second largest after cervical cancer. Until now, the main factor is not yet known what the main causes of breast cancer. This study aimed to determine the relationship of oral contraceptive use with breast cancer incidence rates in the Arifin Achmad Hospital in Riau Province This research uses quantitative research with cross sectional design. The Sample is 67 mothers with oncology cases. Based on 67 respondents mostly mothers with onkolgi cases not using oral contraceptives for > 5 years are 55 (82.09%) and respondents who experienced breast cancer as many as 37 people (55.22%). Analysis of studies that used the chi-square statistical tests with significance level α = 0.05 with 95% confidence interval. The results obtained are H0 is accepted, which is calculated x2 ≤ x2 ≤ 3.841 table is 0.16133. So there is no meaningful relationship between the use of oral contraceptives with an incidence of breast cancer in RSUD Arifin Acmad Riau Province in 2020. From these results, it is expected to the Arifin Achmad Hospital in Riau Province in order to complement the data in medical records in order to facilitate further research.